The fateful alliance : German conservatives and Nazis in 1933 : the Machtergreifung in a new light - Beck, Hermann, 1955- (Berghahn Books, 2008)
On 30 January 1933, Alfred Hugenberg's conservative German National People's Party (DNVP) formed a coalition government with the Nazi Party, thus enabling Hitler to accede to the chancellorship. This book analyzes in detail the complicated relationship between Conservatives and Nazis and offers a re-interpretation of the Nazi seizure of power -- the decisive months between 30 January and 14 July 1933. The Machtergreifung is characterized here as a period of all-pervasive violence and lawlessness with incessant conflicts between Nazis and German Nationals and Nazi attacks on the conservative Bürgertum, a far cry from the traditional depiction of the takeover as a relatively bloodless, virtually sterile assumption of power by one vast impersonal apparatus wresting control from another. The author scrutinizes the revolutionary character of the Nazi seizure of power, the Nazis' attacks on the conservative Bürgertum and its values, and National Socialism's co-optation of conservative symbols of state power to serve radically new goals, while addressing the issue of why the DNVP was complicit in this and paradoxically participated in eroding the foundations of its very own principles and bases of support.--